1989
DOI: 10.1038/bjc.1989.342
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of nuclear DNA content in invasive breast cancer – a study with long-term follow-up

Abstract: Summary The nuclear DNA content of 351 breast carcinomas was determined by flow cytometry from paraffin-embedded tissue to assess the prognostic significance of DNA ploidy, the DNA index (DI) and the S-phase fraction (SPF). The minimum follow-up of the patients was 22 years, and they were all from a defined urban population. DNA ploidy correlated with histological type and grade, mitotic count and nuclear pleomorphism (P<0.0001), and also with axillary nodal status (P=0.0005), tumour necrosis (P=0.001), primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
71
2
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 34 publications
7
71
2
1
Order By: Relevance
“…The near-hyperdiploid DI threshold of 1.13 (PA2) is not a new observation and similar thresholds have been reported elsewhere (25,48). This relatively high DI threshold perhaps explains the relative success of low-resolution technologies in showing DNA ploidy as a strong prognostic variable (49,50).…”
Section: Dna Ploidy Reclassificationsupporting
confidence: 68%
See 1 more Smart Citation
“…The near-hyperdiploid DI threshold of 1.13 (PA2) is not a new observation and similar thresholds have been reported elsewhere (25,48). This relatively high DI threshold perhaps explains the relative success of low-resolution technologies in showing DNA ploidy as a strong prognostic variable (49,50).…”
Section: Dna Ploidy Reclassificationsupporting
confidence: 68%
“…In the 1980s, hundreds of flow cytometry papers demonstrated prognostic significance of DNA ploidy and/or S-phase for many types of solid tumors (16 -22). In particular, many studies showed that S-phase and, in some cases, DNA ploidy could stratify node-negative breast cancer patients into low-and high-risk groups for relapse and death (23)(24)(25), potentially giving oncologists more options in treating this prevalent and deadly disease. Unfortunately, many studies found that S-phase and DNA ploidy were highly correlated.…”
mentioning
confidence: 99%
“…All hospitals, practising physicians and pathological laboratories are requested to report to (WHO, 1981). ILCs were categorized as either 'classical' (n = 157) or 'variant' forms (n = 60) using the criteria published previously (Fechner, 1975;Fisher et al, 1977;Martinez and Azzopardi, 1979 DNA flow cytometry DNA ploidy of 637 carcinomas had been determined by flow cytometry as described previously in conjunction with another study of paraffin-embedded tissue (Toikkanen et al, 1989). The Table 2.…”
Section: Patient Identification and Follow-upmentioning
confidence: 99%
“…This is especially relevant amongst node-negative patients showing a 5-year breast cancer survival rate of 90% (Carter et al, 1989). A growing number of reports indicate that hormone receptor status and proliferative indices could be used to predict the rate of recurrence and survival (Clark et al, 1989;Crowe et al, 1982;Godolphin et al, 1981;Hatschek et al, 1989;Sigurdsson et al, 1990;Skoog et al, 1987;Spyratos et al, 1989;Stal et al, 1989;Thorpe et al, 1987;Toikkanen et al, 1989). While S-phase fraction has been related to the recurrence-free survival of systemically untreated patients with breast cancer (Hery et al, 1987;Silvestrini et al, 1989), conflicting results have been presented on the prognostic value of hormone receptors in the same group of patients.…”
mentioning
confidence: 99%
“…A suspension of isolated nuclei was prepared without washing steps as described by Vindelov et al (1983). The procedure included treatment with a detergent (0.1% NP40), trypsin and RNAse followed by filtering through a 41 ytm nylon mesh.…”
mentioning
confidence: 99%